2023
DOI: 10.3390/pr11010127
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Pretreatment of Jerusalem Artichoke Stalks with Wastewater Recycling and Lignin Recovery for the Biorefinery of Lignocellulosic Biomass

Abstract: Jerusalem artichoke (Helianthus tuberosus L.) is emerging as one of the energy plants considered for biofuel production. Alkali and alkali-involved pretreatment methods have been widely used for the bioconversion of cellulosic materials due to their high sugar yield and low inhibitor release. However, the recovery and treatment of wastewater (black liquor) have been poorly studied. Here, we present a novel two-stage pretreatment process design for recycling black liquor. Jerusalem artichoke stalk (JAS) was fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Transformation of the recovered lignin revealed its potential in a variety of industrial fields. For instance, lignin has been identified as a highly valuable renewable polymer that can be used to manufacture phenolic resins and epoxies [39]. In addition, lignin can function as a binder and dispersant, such as in cement additives.…”
Section: Discussionmentioning
confidence: 99%
“…Transformation of the recovered lignin revealed its potential in a variety of industrial fields. For instance, lignin has been identified as a highly valuable renewable polymer that can be used to manufacture phenolic resins and epoxies [39]. In addition, lignin can function as a binder and dispersant, such as in cement additives.…”
Section: Discussionmentioning
confidence: 99%
“…1 to 5 mm and 100-500 µm sizes of straw were used for further The water-to-ethanol ratio was 3:7 (v/v) to 1:9 (v/v), and the straw-to-liquid ratio was 1:15 to 1:25 with a temperature range of 70 In the first step, 57-69% of the lignin was removed, and this study's main aim was to increase enzyme accessibility. The results showed that the two-step approach was significantly better than the single-step approach Lignin recovery yield was 36.78% [151] The lignin obtained from the organic phase during pretreatment showcased β-O-4 bond characteristics akin to those found in native cellulosic enzyme lignin.…”
Section: Two-step Fractionation For Lignin Extraction and Its Valoriz...mentioning
confidence: 98%
“…The importance of renewable energy sources in the energy balance of Europe has been studied by scientists in [3,12,13]. In [3], researchers estimated the calorific and energy values of Jerusalem artichoke biomass and assessed its potential for bioethanol and biogas production, but the manufacturing process and the quality of the ethanol produced were not studied.…”
mentioning
confidence: 99%
“…In [3], researchers estimated the calorific and energy values of Jerusalem artichoke biomass and assessed its potential for bioethanol and biogas production, but the manufacturing process and the quality of the ethanol produced were not studied. In [12,13], authors present different methods of producing biodiesel from JA tubers-by cultivating microalgae. The researchers studied the oil manufacturing process from microalgae but did not investigate bioethanol production.…”
mentioning
confidence: 99%